2023
DOI: 10.1002/casp.2713
|View full text |Cite
|
Sign up to set email alerts
|

Multiple group memberships protect against anticipatory anxiety for social situations

Abstract: For people with social anxiety, ongoing exposure to feared situations is crucial for both treatment and the prevention of relapse. The COVID‐19 pandemic—with prolonged, often enforced, reductions in people's social contact—reduced such exposure and may thus have exacerbated social anxiety symptoms. In this three‐wave longitudinal study (N = 212) we explored whether people's membership in multiple groups could protect against anticipatory anxiety for, and avoidance of, social situations. In line with our predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…A second theoretical contribution comes from the study of group identities during crisis, which highlights the dual role of group memberships as vulnerabilities and/or sources of resilience. While Donaldson, Cruwys, Dawel, and Chen's (2024) longitudinal study showed that multiple group memberships provided psychological resilience to social anxiety during and after COVID-19, Harkin et al's (2023) qualitative research on older adults with medical conditions highlighted the unique identity-related vulnerabilities of this group. For these older adults, government messaging confirmed negative stereotypes of helplessness and dependency, regardless of their physical condition and deprived them of the active prosocial roles (and associated group memberships) within their local communities that gave many of them a sense of meaning and purpose in retirement.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…A second theoretical contribution comes from the study of group identities during crisis, which highlights the dual role of group memberships as vulnerabilities and/or sources of resilience. While Donaldson, Cruwys, Dawel, and Chen's (2024) longitudinal study showed that multiple group memberships provided psychological resilience to social anxiety during and after COVID-19, Harkin et al's (2023) qualitative research on older adults with medical conditions highlighted the unique identity-related vulnerabilities of this group. For these older adults, government messaging confirmed negative stereotypes of helplessness and dependency, regardless of their physical condition and deprived them of the active prosocial roles (and associated group memberships) within their local communities that gave many of them a sense of meaning and purpose in retirement.…”
Section: Theoretical Contributionsmentioning
confidence: 99%